Hemoglobin Levels and the Associated Factors in the Patients Visiting A University Hospital in Chennai, India - Sadhvi.B1 , Suresh V2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hemoglobin is a protein molecule present in the red blood cells that carries oxygen from the lungs to thebody’s tissues and returns carbon dioxide from the body tissues to the lungs. The normal Hemoglobin levelfor males is 13.5 - 17.5 -grams per deciliter and for females is 12.0 - 15.5 - grams per deciliter. However,Adult men and women have different haemoglobin levels, which are independent of iron status. Estimationof Hemoglobin levels is essential due to several reasons and this research is unique in the aspect of itsimportance in dentistry. This study aims at the assessment of Hemoglobin levels of patients, based ontheir gender visiting Saveetha dental college outpatient department. This is a comparative and descriptivestudy for which the data was obtained from reviewing the patient records. The data collection was fromthe Undergraduate,postgraduate clinics, Saveetha dental college, SIMATS. The data was collected andcompiled followed by its statistical analysis by using the SPSS software by IBM. Out of the total samplesize (1825 cases), various hemoglobin result values obtained were, 5-8 g/dl - 5.2%; 8-12 g/dl - 38.0%;12-16 g/dl -52.3%; and 16-20 g/dl - 4.5%. Where 12-16 g/dl was considered as normal level Hemoglobinlevels among males showed 65.0% under normal range; 27.12% anaemic ; 7.88% above normal level andHemoglobin levels among females showed 35.54 % under normal range ; 64.33 % anaemic ; 0.13% abovenormal level. Chi square test between gender and Hemoglobin result values resulted in a P value < 0.05statistically significant. Hemoglobin levels among the age group 1-31 years were 38.4%; 32-55 years were45.2%; and above 55 years were 16.4%; Chi square tests between various age groups and Hemoglobinresult values resulted in a P value < 0.05 statistically significant. Our study assessed the association ofHemoglobin levels of patients with various parameters such as age, gender and result values. The overallresults show a Male predilection in hemoglobin levels and females having lesser hemoglobin levels thantheir normal range. The study also reveals that Anemia is strongly associated with females when comparedto males and both males and females attain the peak in hemoglobin levels during their young and MiddleAge and gradually come down during old age.